2014
DOI: 10.1186/1471-2393-14-351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trimester-specific and total gestational weight gain on children’s anthropometrics

Abstract: BackgroundGestational weight gain (GWG) has been shown to be a risk factor for overweight in offspring.Aim of this study was to quantify the contributions of trimester-specific and total GWG on offspring’s BMI and waist circumference (WC). This is of interest for the design of interventions targeted at women showing a high GWG in early pregnancy.MethodsIn a retrospective cohort study data on GWG (total and by trimester, exposure), a number of potential confounders, and children’s BMI z-scores and WC (outcomes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…We are adding to the literature by using refined phenotyping to assess child body composition including gold‐standard DXA, as well as showing that the association between first trimester GWG and childhood adiposity is stronger in children born to women who have obesity before entering pregnancy. We also demonstrated for the first time that faster second trimester GWG is associated with greater lean mass, particularly in women with normal weight, which might explain some prior reports of an association between mid‐pregnancy GWG and childhood BMI , a measure that reflects both lean and fat mass.…”
Section: Discussionsupporting
confidence: 75%
“…We are adding to the literature by using refined phenotyping to assess child body composition including gold‐standard DXA, as well as showing that the association between first trimester GWG and childhood adiposity is stronger in children born to women who have obesity before entering pregnancy. We also demonstrated for the first time that faster second trimester GWG is associated with greater lean mass, particularly in women with normal weight, which might explain some prior reports of an association between mid‐pregnancy GWG and childhood BMI , a measure that reflects both lean and fat mass.…”
Section: Discussionsupporting
confidence: 75%
“…Our results contribute evidence on the effects of low GWG on birthweight among women who were underweight or normal weight before pregnancy. As previous studies 11,12,33,35,36 and other life course studies have also shown an association between GWG in the earlier gestation period and infant anthropometrics, [13][14][15][16][17] our findings emphasize that fetal development is especially susceptible to low GWG in the second trimester.…”
Section: Discussionsupporting
confidence: 84%
“…Recent analyses of the trimester-specific effects of GWG have employed successive weight measurements. [11][12][13][14][15][16][17] In order to improve perinatal management and facilitate healthy fetal development, it is necessary to identify the critical periods that can influence birth outcomes and to quantify those effects. The analysis of successive GWG measurements can provide insight into this important topic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pre-BMI, GWG also plays an important role in determining NBW. In studies of the association of GWG and NBW, it has been widely found that the former positively influenced the latter (Institute of Medicine and National Research Council, 2009), and some studies have further discovered that each kilogram of weight gain in the second trimester has the strongest effect among the three trimesters (Abrams and Selvin, 1995;Institute of Medicine and National Research Council, 2009;Bayer et al, 2014). The present study came to a similar conclusion that GWG has a positive effect on NBW with weight gain in the second trimester the most prominent.…”
Section: Fig 2 Proportions Of Women With Gestational Weight Gain (Gwmentioning
confidence: 99%